Teacher readiness for the prevention and correction of emotional disturbance in primary school children with attention deficit hyperactivity disorder - G. V. Valiulina (Образование и наука)
Introduction. Psychological and pedagogical support for learners with attention deficit hyperactivity disorder (ADHD) has currently become crucial in the Russian and foreign systems of education. The problem has been caused by the increasing number of children suffering from this disorder and insufficient readiness of a modern teacher to implement preventive and corrective work with the specified category of school students in a comprehensive school. One of the most common complications of ADHD in primary school children, along with learning difficulties, are emotional disorders (inadequately underestimated or overestimated self-esteem, anxiety, depression, affective outbursts). The current situation in education actuates the necessity of modern teacher’s readiness to prevent complications of ADHD as well as to provide corrective help to children with this disorder.Aim. The present research aims to determine the structure of the future teacher’s readiness to prevent and correct emotional disorders in primary school children with ADHD in the comprehensive school environment.Methodology and research methods. As methodological basis of the research served the activity-based, systemic, and competency-based approaches. Two groups of methods were applied in the study: theoretical (analysis, synthesis, classification, and generalisation) and empirical (survey methods, documentation analysis). The research methodology included the author’s questionnaire “Identification of Theoretical, Methodological and Psychological Difficulties in Primary School Teachers to Prevent and Correct Emotional Disorders in Junior Schoolchildren with ADHD”, the techniques “Self-Assessment of Empathic Abilities” (Yu. M. Orlova, Yu. N. Emelyanova) and “The Psychological Portrait of a Teacher” (Z. V. Rezapkina, G. V. Rezapkina). In addition, the interviews were conducted.Results. The analysis of diagnostic results showed that the respondents had superficial theoretical and methodological knowledge about psychophysiological characteristics of children with ADHD, as well as about children’s education organisation in a comprehensive school. On average, less than half of the respondents gave correct answers to the questions of the theoretical block. In the methodological block, the lack of professional knowledge on the organisation of education and upbringing of children with ADHD in a comprehensive school was revealed.The study identified the following organisational and content problems related to the prevention and correction of emotional disturbance in primary school children with ADHD in a comprehensive school: the lack of psychological and pedagogical support for this category of school children; a low level of theoretical and methodological knowledge of school teachers in the field of psychological and pedagogical support for school students with ADHD; the shortage of teachers’ skills and abilities to prevent and correct emotional disorders; the deficit of special programmes for psychological and pedagogical support of students in a comprehensive school; teacher’s unwillingness to work with this category of students; indisposition of parents having children with ADHD to cooperate with the teacher regarding their child’s education and upbringing.Scientific novelty. The structure of the future teacher’s readiness to prevent and correct emotional disorders in younger students ADHD in a comprehensive school was determined on the basis of the described professional qualities of a modern teacher; it includes the following components: motivational, theoretical-methodological, psycho-pedagogical, and methodical. Qualitative characteristics of these structural components were given to determine the possibility of preventing and correcting emotional disorders in younger schoolchildren with ADHD.Practical significance. The research results can be applied in the process of primary school teachers training in the system of higher education, as well as in the system of additional professional education to implement teacher training programmes on key issues of modern education in general, and, in particular, on the problems of the prevention and correction of emotional disturbance in primary school children with ADHD in the comprehensive school.